The effect of benzocaine and ketoprofen gels on pain during fixed orthodontic appliance treatment: a randomised, double-blind, crossover trial - Eslamian Ladan; Borzabadi-Farahani Ali; Gholami Hadi (Sciendo, 2016)
To compare the analgesic effect of topical benzocaine (5%) and ketoprofen (1.60 mg/mL) after 2 mm activation of 7 mm long delta loops used for maxillary en-masse orthodontic space closure.